(untitled) (diségno, 2024)
Scale models have been an integral part of architectural activity from its origins and continue to be so today, despite significant advancements in digital graphics. There are several reasons for the enduring presence of these small architectural objects, which have adapted to various conditions of creation and different historical moments. Despite the rapid advancements in infographic media and even virtual reality related to architecture, the model remains an object of interest in major architectural offices around the world. Thus, models continue to captivate the public with their unique magic and characteristics in architecture exhibitions, whether related to contemporary architects [1] or ancient ones [2]. The intention now is to consider the factor of the material with which they are built, a crucial issue from various aspects inherent to the model: the scale relationship, the reference to the real or projected object, the artisanal relationship with other trades, the presumed formal or sculptural autonomy, and ultimately, the very spirit of the times or Zeitgeist in which each model is framed.